Gender Gaps across the Spectrum of Development: Local Talent and Firm Productivity - Nava Ashraf; Oriana Bandiera; Virginia Minni; Víctor Quintas-Martínez (Institute of Labor Economics (IZA), 2024)
We ask whether the gendered division of work affects firm productivity across the spectrum of economic development. Personnel records of over 100,000 individuals hired by a global firm that operates in 100 countries reveal that the performance of female employees is higher where women are underrepresented in the candidate pool. This implies productivity gains from hiring more women, but realizing them would require increasing women's pay relative to men. The findings highlight how unequal gender norms in local labor markets create an equity-efficiency trade-off inside the firm, particularly in low-income countries with conservative gender norms.
Keywords: O12; O15; M5; 330; female labor force participation; multinationals; local labor markets; gender pay gap; firm productivity